MANAJEMEN FISIOTERAPI DALAM MENINGKATKAN KETERBATASAN LGS DAN KEKUATAN OTOT PADA KASUS POST OP ACL FASE 2 DI RSUD KMRT WONGSONEGORO SEMARANG: STUDI KASUS - Diah Ayu Vitaloka,; Wijianto,; Halim Mardianto, (Jurnal Cakrawala Ilmiah, 2023)
Anterior Cruciate Ligament (ACL) injury is one of the most common injuries among sports athletes. This injury is caused by a tear in the ligament which is characterized by knee instability and a popping “pop” sound after the injury. Reconstructing the ACL is usually done by grafting the disconnected tissue. Patients after ACL reconstruction experience symptoms of complications such as pain, decreased joint range of motion, and muscle weakness. Purpose: This study aims to determine the effect of providing physiotherapy interventions such as cryotherapy, patella mobilization, ROM exercise, and strengthening exercises using resistance bands. Method: The research method was carried out directly on 1 respondent with post-op ACL Phase 2 in 4 therapy sessions. Result: After 4 sessions of therapy, the results showed a decrease in pain, an increase in the value of the range of motion of the joints, and an increase in muscle strength. Conclusion: there is an effect of providing physiotherapy management to reduce pain, increase joint range of motion, and increase muscle strength.